P001 Communication from the cerebellum to the neocortex during sleep spindles. (19th November 2019) - Xu, Wei; Carvalho, Felipe De; Clarke, Alexander; Jackson, Andrew
Abstract : Introduction: Surprisingly little is known about neural activity in the sleeping cerebellum. 5 17 Using long-term wireless recordings, we have made routine recordings of local field potentials (LFPs) and action potentials for the entirety of natural sleep in non-human primates. Methods: We were able to record simultaneously from the primary motor cortex (M1), the thalamus and the cerebellum using both rigid multi-contact linear electrode arrays and flexible microwires. 11 12 Recording for the entirety of the natural sleep was achieved using a custom-made wearable device. Results: We find that the M1 and cerebellum communicate with each other during sleep, 13 14 with cerebellum-to-M1 signals passing via the thalamus. We find that both M1 and cerebellar neuronal firings are broadly synchronous and phase-locked to the sleep cycle. 7 Additionally, both spikes and LFPs in M1 and cerebellum also show coherence at slow (<1Hz), delta (1-4Hz) and alpha (7–15Hz) frequencies. 8 15 16 We also see phase-locking between the spikes of M1 and the LFPs of the cerebellum (and vice versa) at these same frequencies. Using Granger causality analysis on the LFPs we were able to observe directed connectivity from motor cortex to the cerebellum in deep sleep. This suggested a neocortical origin of slow oscillations. By contrast, sleep spindles (in the alpha frequency range) in light sleep revealed a causal influence from the cerebellum to motor cortex, going via the thalamus. Discussion: Our results shed new light on the mechanisms of sleep spindle generation 9 and show that the cerebellum is an active participant of sleep. We postulate that the cerebello-thalamo-neocortical pathways is implicated in sleep-dependent consolidation of procedural learning. 1-4 6 18-20 References: Bastian AJ. Learning to predict the future: the cerebellum adapts feedforward movement control. Current opinion in neurobiology 2006;16(6):645–9. Nishida M, Walker MP. Daytime naps, motor memory consolidation and regionally specific sleep spindles. PloS one 2007;2(4):e341. Fogel S, Albouy G, King BR, Lungu O, Vien C, Bore A, et al. Reactivation or transformation? Motor memory consolidation associated with cerebral activation time-locked to sleep spindles. PloS one 2017;12(4):e0174755. Diekelmann S, Born J. The memory function of sleep. Nature reviews Neuroscience 2010;11(2):114–26. Canto CB, Onuki Y, Bruinsma B, van der Werf YD, De Zeeuw CI. The Sleeping Cerebellum. Trends Neurosci 2017;40(5):309–23. Latchoumane CV, Ngo HV, Born J, Shin HS. Thalamic Spindles Promote Memory Formation during Sleep through Triple Phase-Locking of Cortical, Thalamic, and Hippocampal Rhythms. Neuron 2017;95(2):424–35.e6. Mano N. Changes of simple and complex spike activity of cerebellar purkinje cells with sleep and waking. Science 1970;170(3964):1325–7. Staresina BP, Bergmann TO, Bonnefond M, van der Meij R, Jensen O, Deuker L, et al. Hierarchical nesting of slow oscillations, spindles and ripples in the human hippocampus during sleep. Nature neuroscience 2015;18(11):1679–86. Luthi A. Sleep Spindles: Where They Come From, What They Do. The Neuroscientist : a review journal bringing neurobiology, neurology and psychiatry 2014;20(3):243–56. Xu W, de Carvalho F, Jackson A. Sequential neural activity in primary motor cortex during sleep. J Neurosci 2019. Kelly RM, Strick PL. Cerebellar loops with motor cortex and prefrontal cortex of a nonhuman primate. J Neurosci 2003;23 (23):8432–44. Holdefer RN, Miller LE, Chen LL, Houk JC. Functional connectivity between cerebellum and primary motor cortex in the awake monkey. Journal of neurophysiology 2000;84 (1):585–90. Rowland NC, Goldberg JA, Jaeger D. Cortico-cerebellar coherence and causal connectivity during slow-wave activity. Neuroscience 2010;166 (2):698–711. Watson TC, Becker N, Apps R, Jones MW. Back to front: cerebellar connections and interactions with the prefrontal cortex. Frontiers in systems neuroscience 2014;8 :4. D'Angelo E, Koekkoek SK, Lombardo P, Solinas S, Ros E, Garrido J, et al. Timing in the cerebellum: oscillations and resonance in the granular layer. Neuroscience 2009;162 (3):805–15. Courtemanche R, Robinson JC, Aponte DI. Linking oscillations in cerebellar circuits. Frontiers in neural circuits 2013;7 :125. Seshagiri DV, Botta R, Sasidharan A, Kumar Pal P, Jain S, Yadav R, et al. Assessment of Sleep Spindle Density among Genetically Positive Spinocerebellar Ataxias Types 1, 2, and 3 Patients. Annals of neurosciences 2018;25 (2):106–11. Manoach DS, Thakkar KN, Stroynowski E, Ely A, McKinley SK, Wamsley E, et al. Reduced overnight consolidation of procedural learning in chronic medicated schizophrenia is related to specific sleep stages. Journal of psychiatric research 2010;44 (2):112–20. Farmer CA, Chilakamarri P, Thurm AE, Swedo SE, Holmes GL, Buckley AW. Spindle activity in young children with autism, developmental delay, or typical development. Neurology 2018;91 (2):e112–e22. Russek EM, Momennejad I, Botvinick MM, Gershman SJ, Daw ND. Predictive representations can link model-based reinforcement learning to model-free mechanisms. PLoS computational biology 2017;13 (9):e1005768.